(untitled) (Journal of Scientific Research, 2024)
The transportation trailer system comprises numerous delicate components that require careful handling throughout transit. During transportation, the system is subjected to vibrations and shock loads resulting from road conditions, trailer acceleration, and deceleration. If these loads are transferred to the system, it could adversely affect many of its elements, particularly at resonance. To mitigate such vibration-induced stress on the system, a vibration isolation system has been designed and analyzed. The transportation system is modelled and analyzed using the finite element method. The Power Spectral Density (PSD) based on ISO-8606 standard for random road profiles is utilized for spectrum analysis computations in the Finite Element Analysis (FEA). Natural frequencies in the transportation system with isolator obtained from the finite element analysis are compared with the mathematically calculated values and any discrepancies are reported as error percentages.